Individuals with chronic ankle instability exhibit dynamic postural stability deficits and altered unilateral landing biomechanics: A systematic review. (May 2019) - Simpson, Jeffrey D.; Stewart, Ethan M.; Macias, David M.; Chander, Harish; Knight, Adam C.
Abstract: Objective: To evaluate the literature regarding unilateral landing biomechanics and dynamic postural stability in individuals with and without chronic ankle instability (CAI). Methods: Four online databases (PubMed, ScienceDirect, Scopus, and SportDiscus) were searched from the earliest records to 31 January 2018, as well as reference sections of related journal articles, to complete the systematic search. Studies investigating the influence of CAI on unilateral landing biomechanics and dynamic postural stability were systematically reviewed and evaluated. Results: Twenty articles met the criteria and were included in the systematic review. Individuals with CAI were found to have deficits in dynamic postural stability on the affected limb with medium to large effect sizes and altered lower extremity kinematics, most notably in the ankle and knee, with medium to large effect sizes. Additionally, greater loading rates and peak ground reaction forces, in addition to reductions in ankle muscle activity were also found in individuals with CAI during unilateral jump-landing tasks. Conclusions: Individuals with CAI demonstrate dynamic postural stability deficits, lower extremity kinematic alterations, and reduced neuromuscular control during unilateral jump-landings. These are likely factors that contribute recurrent lateral ankle sprain injuries during dynamic activity in individuals with CAI. Highlights: Individuals with CAI demonstrate dynamic postural stability deficts. Altered kinematic patterns and neuromuscular control are associated with CAI. Clinicians should aim to restore altered movement patterns during rehabilitation. More studies are needed to understand the link between kinetics and injury.